BREASTFEEDING KNOWLEDGE, ATTITUDE, AND PRACTICES IN MOTHERS OF INFANT OF 0–12 MONTHS OF AGE - AGRAWAL, VIJAY; KUMAR MEENA, SUSHIL; AGRAWAL, CHARUSMITA; BANSAL, SHARAD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The aim of the study was to evaluate current status of knowledge, attitude, and breastfeeding practices in mothers of infant of 0–12 months of age. Methods: After ethical approval, this questionnaire-based observational study was carried out for a period of 1.5 year in Department of Paediatrics, SMS Medical College and Attached Hospitals, Jaipur. All mothers of the infant of age 0–12 months brought to department were included in the study. Twenty-five questions related to knowledge, attitude, and practices were used to get data in a questionnaire. Results: Out of total 500 study participants, maximum 156 (31.2%) were in age group of 26–30 years. Mean score of knowledge and attitude was 11.55±4.17. In the present study, no significant difference was found between different age group, religion, age of the children, and mode of delivery for knowledge and attitude score. (p>0.05) Significantly higher knowledge and attitude score was found among urban participants, who lived in joint family, having higher education, more antenatal visits, and whose delivery took place in private hospital (p˂0.05). Conclusion: Knowledge, attitude, and practices for breast feeding were found significantly more in mothers of urban residence, of higher education level, having good occupation, live in joint family, and went for more antenatal visits and who went for delivery at private hospital.